Rare sex or out of reach equilibrium? The dynamics of FIS in partially clonal organisms. Issue 1 (December 2016) - Reichel, Katja; Masson, Jean-Pierre; Malrieu, Florent; Arnaud-Haond, Sophie; Stoeckel, Solenn
Abstract Background Partially clonal organisms are very common in nature, yet the influence of partial asexuality on the temporal dynamics of genetic diversity remains poorly understood. Mathematical models accounting for clonality predict deviations only for extremely rare sex and only towards mean inbreeding coefficient F IS ¯ < 0 F_IS<0 . Yet in partially clonal species, bothF IS < 0 andF IS > 0 are frequently observed also in populations where there is evidence for a significant amount of sexual reproduction. Here, we studied the joint effects of partial clonality, mutation and genetic drift with a state-and-time discrete Markov chain model to describe the dynamics ofF IS over time under increasing rates of clonality. Results Results of the mathematical model and simulations show that partial clonality slows down the asymptotic convergence toF IS = 0. Thus, although clonality alone does not lead to departures from Hardy-Weinberg expectations once reached the final equilibrium state, both negative and positiveF IS values can arise transiently even at intermediate rates of clonality. More importantly, such "transient" departures from Hardy Weinberg proportions may last long as clonality tunes up the temporal variation ofF IS and reduces its rate of change over time, leading to a hyperbolic increase of the maximal time needed to reach the final mean F IS, ∞ ¯ F_IS, ∞ value expected at equilibrium. Conclusion Our results argue for a dynamical interpretation ofF IS in clonal populations. Negative values cannot be interpreted as unequivocal evidence for extremely scarce sex but also as intermediate rates of clonality in finite populations. Complementary observations (e.g. frequency distribution of multiloci genotypes, population history) or time series data may help to discriminate between different possible conclusions on the extent of clonality when mean F IS ¯ F_IS values deviating from zero and/or a large variation ofF IS over loci are observed.